Systematic review and meta-analysis of surgery for hilar cholangiocarcinoma with arterial resection. Issue 10 (October 2022) - Rebelo, Artur; Friedrichs, Juliane; Grilli, Maurizio; Wahbeh, Nour; Partsakhashvili, Jumber; Ukkat, Jörg; Klose, Johannes; Ronellenfitsch, Ulrich; Kleeff, Jörg
Abstract: Background: With the advances in multimodality treatment, an analysis of the outcome of arterial resections (AR) in surgery of cholangiocarcinoma is lacking. The aim of this meta-analysis was to summarize the currently available evidence onof AR for the treatment of cholangiocarcinoma. Methods: A systematic literature search was carried out according to PRISMA guidelines. Results: 10 retrospective cohort studies published from 2007 to 2020 with 2530 patients (408 AR group and 2122 control group) were identified. Higher in-hospital mortality rates (6.8% vs 3.3%, OR 2.65, 95% CI [1.27; 5.32], p = 0.009), higher morbidity rates (Clavien-Dindo classification ≥3 ) (52% vs 47%, OR 1.44, 95% CI [1.02; 1.75], p = 0.04) and lower 1-year, 3-year and 5-year survival rates (54% vs 69%, OR 0.55, 95% CI [0.34; 0.91 p = 0.02), (34% vs 38%, OR 0.74, 95% CI [0.55; 0.98, p = 0.03), (18% vs 29%, OR 0.54, 95% CI [0.39; 0.75, p = 0.0002) were observed in the AR group when compared to the control group. Conclusion: Evidence from non-randomized studies shows a higher morbidity and mortality and shorter long-term survival in patients undergoing AR. However, the results are prone to selection bias, and only randomized trials comparing AR and palliative treatments AR might reveal a possible benefit of AR. Systematic review registration: PROSPERO ID 223396.